Ion-Scale Sideband Waves and Filament Formation: Alfvénic Impact on Heliospheric Plasma Turbulence - Narita, Yasuhito; Motschmann, Uwe (Frontiers in Physics, 2017)
A mini-review is given about two recent discoveries in the solar wind turbulence research on ion-kinetic scales: the existence of sideband waves (or breakdown of the linear mode wave picture) and the wavevector anisotropy leading to a persistent filament formation in a wide range of plasma beta.